(untitled) (Journal of Forest and Livelihood, 2016)
The paper explores the intersectionalities of conflict in natural resource governance between the state authorities, indigenous Tharu and Sonaha people in general and women in particular in the buffer zone (BZ) of the Bardia National Park (BNP). Drawing upon the experiences of two buffer zone user groups at BNP’s BZs, this paper argues that the gendered nature of protected area (PA) management and governance affects the Tharu and Sonaha women and aggravates their exposure to multiple vulnerabilities posed by park policies and authorities. The paper also demonstrates that the genuine participation of Tharu and Sonaha women in the management structures of BZ is limited; and attempts to contribute in the gender dimensions of (PA) management and governance.